1998
DOI: 10.1677/joe.0.1590233
|View full text |Cite
|
Sign up to set email alerts
|

11beta-hydroxysteroid dehydrogenase is a predominant reductase in intact rat Leydig cells

Abstract: Abstract11 -Hydroxysteroid dehydrogenases (11 -HSDs) interconvert active corticosterone and inert 11-dehydrocorticosterone. In tissue homogenates, 11 -HSD type 1 (11 -HSD-1) exhibits both 11 -dehydrogenase (corticosterone inactivating) and 11 -reductase (corticosterone regenerating) activities, whereas 11 -HSD type 2 (11 -HSD-2) is an exclusive dehydrogenase. In the rat testis, 11 -HSD has been proposed to reduce glucocorticoid inhibition of testosterone production, promoting puberty and fertility. This hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 40 publications
2
27
1
1
Order By: Relevance
“…In other tissues, 11 -dehydrogenase activity has been reported in intact cell preparations with the direction of 11 -HSD1 catalysis appearing to vary according to physiological or developmental status of a particular cell type. In Leydig and neuronal cells, as well as in human bone, both 11 -dehydrogenase and oxo-reductase activities have been observed (Ge et al 1997, Leckie et al 1998, Jellinck et al 1999, Cooper et al 2000. Only oxo-reductase activity has been detected in kidney cells of monkey origin (Cos-7) transiently transfected with rat 11 -HSD1 cDNA (Low et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In other tissues, 11 -dehydrogenase activity has been reported in intact cell preparations with the direction of 11 -HSD1 catalysis appearing to vary according to physiological or developmental status of a particular cell type. In Leydig and neuronal cells, as well as in human bone, both 11 -dehydrogenase and oxo-reductase activities have been observed (Ge et al 1997, Leckie et al 1998, Jellinck et al 1999, Cooper et al 2000. Only oxo-reductase activity has been detected in kidney cells of monkey origin (Cos-7) transiently transfected with rat 11 -HSD1 cDNA (Low et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This applies in primary cultures of cells from liver (Jamieson et al 1995), adipose tissue (Bujalska et al 1997), lung (Hundertmark et al 1995, hippocampus (Rajan et al 1996), and vascular smooth muscle (Brem et al 1995). In a few studies, for example in Leydig cells, 11 -dehydrogenase activity has been reported in apparently intact cell preparations (Phillips et al 1989), but others have found predominant 11 -reduction (Leckie et al 1998) and argued that Figure 2 The enzymatic reactions of 11 -HSD1. 11 -HSD1 activity levels can be determined by the urinary ratio THF+alloTHF:THE.…”
Section: Set-point Of 11 -Hsd1 Activitymentioning
confidence: 99%
“…Discrepancies in the literature on the relative predominance oxidation and reduction may have arisen from the use of incubation periods longer than ten minutes, given that linearity of the reaction velocities in assays of intact Leydig cells, necessary for accurate estimation of enzyme kinetic parameters, is lost after ten minutes. Culture of Leydig cells for several days prior to measurement of enzyme activity results in sharp declines in 11βHSD1 oxidative activity and predominance of the reductase [53]. This is not surprising because the two activities are inversely regulated: in rat Leydig cells, protein kinase C increases 11βHSD1 oxidation and inhibits reduction [54].…”
Section: A Rapid Action Of Glucocorticoids Via 11βhsd1mentioning
confidence: 99%